Public policies and financing for Mexican SMEs in the face of the Covid19 pandemic - Manuel Tregear (Panorama Económico, 2023)
Background and objectives: This article is focused on understanding the impact of public policies on Small and Medium Enterprises, especially in terms of financial support in the face of the crisis caused by the Covid19 pandemic. To this end, the hypothesis is presented that this support was not sufficient to restore the performance of these companies.